9x-17=3x+43

Simple and best practice solution for 9x-17=3x+43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-17=3x+43 equation:


Simplifying
9x + -17 = 3x + 43

Reorder the terms:
-17 + 9x = 3x + 43

Reorder the terms:
-17 + 9x = 43 + 3x

Solving
-17 + 9x = 43 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-17 + 9x + -3x = 43 + 3x + -3x

Combine like terms: 9x + -3x = 6x
-17 + 6x = 43 + 3x + -3x

Combine like terms: 3x + -3x = 0
-17 + 6x = 43 + 0
-17 + 6x = 43

Add '17' to each side of the equation.
-17 + 17 + 6x = 43 + 17

Combine like terms: -17 + 17 = 0
0 + 6x = 43 + 17
6x = 43 + 17

Combine like terms: 43 + 17 = 60
6x = 60

Divide each side by '6'.
x = 10

Simplifying
x = 10

See similar equations:

| f(x)=3ln(x) | | F(x)=-1/5x^2 | | f(x)=x^3ln(x) | | 3.2x+6-2.2x=9 | | 50=1x+3 | | 6(x-1)+5=0 | | x-4=4.79 | | 3x^2-7x+3y^2-8y=0 | | 4f-48=325 | | 6m+13=265 | | -4(5-7r)+7=31+6r | | 4log(x-6)=8 | | 10a^2+a-2= | | 4z+37=325 | | 6x^3+9x^2+3x=0 | | -7+x-3x=37 | | -0.3+4.38=-0.1+6.78 | | 8(x+4)-4x-4x=2(2x+3)-14 | | 7d-2=40 | | -26=6(u-4)-8u | | 5x-37=98 | | 0.6x+12.9=x-6.46 | | 54x^2-90x-300=0 | | (x-.6)(2x+3)=0 | | 3x+54=x^2 | | 16-3x=-10 | | -0.1x+1.12=-0.5+2.32 | | -14=3(x-6)-7x | | 4f-48=92 | | 3/4×12= | | 4a^2+19a-63=0 | | -9+5x=4 |

Equations solver categories